Pre-Service English Teachers’ Perceptions on The Use of Google Translate for Academic Writing - Aininda Nur Baiti; Fahrur Rozi (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2026)
Abstract: This qualitative case study aimed to determine how English teacher candidates feel about using Google Translate for academic writing. It is focused on thesis writing the final project. A total of 33 pre-service English teachers’ from Walisongo State University in Semarang, Indonesia, took part in the study. Purposive sampling was used to select participants based on three factors: 1) Writing a final project; 2) Being a pre-service English teacher; and 3) Using Google Translate for the final project. There are five participants out of the 33 who agreed to an interview. Google-form based questionnaires and online interviews were used to collect data, which were then analyzed by frequency analysis and thematic analysis based on the metacognition model. Based on the research finding, 84,8% of pre-service English teachers agree, 3% strongly agree, and only 12,1% disagree that in every translation procedure, Google Translate is very helpful. Using several easy-to-use, ubiquitous, and easily downloadable features, Google Translate offered translation services for their thesis. They were able to complete their thesis because using Google Translate made them more confident in their writing. This study explains how pre-service English teachers perceive the use of Google Translate to help with their final project (thesis) in academic writing. Future researchers can thoroughly examine the advantages and disadvantages of using Google Translate and also explore the use of Google Translate in other areas for English language learning. Keywords: Pre-service English Teacher; Perceptions; Google Translate; Academic Writing